LIGAND-BASED VIRTUAL SCREENING OF FDA-APPROVED DRUGS TO IDENTIFY NEW INHIBITORS AGAINST LACTATE DEHYDROGENASE ENZYME OF MALARIA PARASITES - ODHAR, HASANAIN ABDULHAMEED; HASHIM, AHMED FADHIL; HUMADI, SUHAD SAMI; AHJEL, SALAM WAHEED (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this study is to computationally repurpose FDA-approved drugs as potential inhibitors of the Plasmodium falciparum lactate dehydrogenase (PfLDH) by competing with the cofactor NADH. Methods: In this in silico study, we have virtually screened a library of FDA-approved drugs for structural similarity to the dihydro nicotinamide adenine dinucleotide (NADH). Then, the top hits were further assessed for clinical safety and by application of molecular docking and dynamics simulation. Results: Ligand-based virtual screening reports that the antibiotic Novobiocin has a good similarity to the cofactor NADH with a score of 0.7. Also, molecular docking study indicates that Novobiocin may has the ability to interact with PfLDH enzyme with a docking energy of-8.8 Kcal/mol. However, during molecular dynamics (MD) simulation, the mean ligand proximity root mean square deviation (RMSD) and binding energy for Novobiocin were 4.3 Angstrom and-37.45 Kcal/mol, respectively. These MD simulation parameters are inferior to those recorded for NADH molecule during 50 nanosecond intervals. Conclusion: The antibiotic Novobiocin may serve as a potential lead candidate toward the design of novel antimalarial agents. However, further evaluation of Novobiocin may be recommended to affirm its capacity against PfLDH enzyme.